PENYESUAIAN DIRI MAHASISWA DALAM PELAKSANAAN PPLBK MASYARAKAT DI KELURAHAN LUBUK MINTURUN KECAMATAN KOTO TANGAH PADANG (Studi pada Mahasiswa BK Angkatan 2010 STKIP PGRI Sumatera Barat) - Afdiwahyuni, Sri Rati; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
This research is motivated by the students in the implementation of the adjustment in the Village Community PPLBK Lubuk Minturun. The objective is to describe: (1) the adjustment of student in the implementation of community PPLBK seen from a personal aspect, (2) the adjusment of student in the implementation of community PPLBK viewed from a social aspect. This research is a descriptive qualitative research. Informants in this study were as many as 3 students and community supporters informant by 4 people, along with officials in the Village headman Lubuk Minturun. Data were collected through interviews and documentation. The results showed that students attempt to reach adjustment on the environment is very good. In this study explains how the adjustment to the student community from the aspects of personal and social aspects. Based on the results seen from a personal aspect that students have a good emotional stability, have pruduktif attitude in developing themselves and have empathy, friendship and interpersonal relationships. While the views of the social aspects that students have the steadiness atmosphere of togetherness with others, students also have the ability to understand others and actively participate in an activity and a willingness to work together with the community.